PERAN KEPERCAYAAN MEMEDIASI PENGARUH CUSTOMER EXPERIENCE TERHADAP REPURCHASE INTENTION KONSUMEN SHOPEE - Dananjaya, Putu Arya; Giantari, I Gst. Ayu Kt. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023DO - 10.24843/EEB.2023.v12.i09.p10, 2023)
Technological advances make changes in many fields as well as changes in consumer shopping behavior where there is a shifting from conventional shopping to shopping online and making competition between e-commerce increase. To win the competition, e-commerce must be able to make users reuse services in the future. This study aim to examines the role of trust in mediating customers experiences on repurchases intentions in Shopee consumers. The population in this study are all Shopee application users who are domiciled in Denpasar City. The sampling technique used in is proportional sampling with 120 respondents. Data collected using a questionnaire. This research uses path analysis. Results show customers experiences has a positive significant effects on repurchases intentions, customers experiences has a positive significant effects on trusts, trusts has a positive significant effects on repurchases intention and trusts is a mediating variable between customers experiences on repurchases intentions on shopee consumers.